2014
DOI: 10.1111/dsu.12474
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hypoxia in Scar Tissue During Human Hypertrophic Scar Progression

Abstract: Hypoxia is dynamic in scar tissue and is possibly correlated with scar formation and regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 29 publications
7
31
0
Order By: Relevance
“…The size of the vascular network (VAR and MVD) found in our study in healthy skin is consistent with values found in previous studies [34,35]. VAR and MVD start to expand significantly 24 h after LTB 4 challenge and continue to expand during the remaining experiment.…”
Section: Discussionsupporting
confidence: 93%
“…The size of the vascular network (VAR and MVD) found in our study in healthy skin is consistent with values found in previous studies [34,35]. VAR and MVD start to expand significantly 24 h after LTB 4 challenge and continue to expand during the remaining experiment.…”
Section: Discussionsupporting
confidence: 93%
“…MMP16 is part of the matrix metalloproteinase (MMP) gene family that is directly relevant to fibrosis [23]. Previous reports demonstrated that severe hypoxia existed in regressive scars, and oxygen levels return to normal in mature scars, findings that are consistent with dynamic changes in microvessel density [5]. Our results revealed that lncRNA8975-1 and AC097662.2 expression were decreased, whereas RP11-586K2.1 expression was increased during regression from a regressive scar to mature scar.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin & eosin staining was performed as previously described [5]. Briefly, tissue samples were fixed for 2 hours in 4% paraformaldehyde in phosphate buffered saline (PBS), stored overnight in 10% formalin, and paraffin-embedded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In the hypoxic state, HIF-1 enters the nucleus, binds to the hypoxia responding elements, and regulates the transcription and expression of its downstream factors such as VEGF. There also exists a synergism between these cytokines.…”
Section: Relationship Between Cytokinesmentioning
confidence: 99%